Students Repository: Online archive for academic exercise, dissertation and theses - Mohd Faizal, H.; Ilina Syazwani, M. (2015)
Academic exercises, dissertations and theses are information resources which are really useful to students, lecturers and even researchers. It is generally understood that these types of information resources are copyrighted materials whereby authors own the copyright. Obtaining the full text of these materials online especially in open access platforms is very difficult. As we all know, open access is the current trend of information delivery and there are lots of advantages. Most of the academic libraries in Malaysia are allowed to share only few pages in any open access platform due to policy of the organization/university and the copyright act. However, open access really helps the university to be recognized, and at the same time authors can create networking by showcasing their research output. Considering the benefits of open access, University of Malaya (UM) believes that all written works of UM students should be open to public. Students are given options to transfer the ownership. To support that mission, University of Malaya Library (UML) has initiated a Students Repository portal which acts as an online archive for academic exercises, dissertations and theses. UML used Eprints as a platform to make these materials accessible. This article shares the experiences of UML’s initiative in creating this open access platform for these materials. There were several issues that needed to be ironed out such as copyright policies, technical parts, storage, metadata scheme and maintenance. Making these types of information resources open access was challenging due to reasons such as confidential data, funders and also the quality of the research output. UML conducted a simple survey to highlight several thoughts by academicians and students regarding this issue.